High Prevalence of Adrenal Insufficiency in Patients with Sickle Cell Disease: Results from a Community Hospital in the U.S. - Makino, J.; Ndzengue, A.; Adekolujo, S.; Tipu, A.; Dogar, U. M.; Mezher, H.; Sivasambu, B.; Trauber, D.; Guillaume, E.; Jaffe, E. A.; Shiferaw-Deribe, Z. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Despite the low prevalence (0.008%) of adrenal insufficiency (AI) in the general population, this disorder was recently diagnosed in a substantial number of sickle cell disease (SCD) patients at our hospital. The main objective of this study was to assess the prevalence of AI in SCD patients.All adult patients admitted to the Department of Medicine at Interfaith Medical Center from October 2010 to November 2011 were eligible for this retrospective study. Medical records of adult SCD patients hospitalized for painful crisis and who had undergone cosyntropin testing were reviewed. Adult non-SCD patients hospitalized for painful crisis and who had undergone cosyntropin testing served as controls. The result of the cosyntropin test was the primary outcome. The prevalence of positive cosyntropin tests was compared between the 2 groups by using Student’s t-test, and odds ratios.62 adult SCD patients were enrolled in the study. 15 underwent cosyntropin testing and 12 (19.4%) of these patients were found to have AI. AI was also diagnosed in 1 of 1 340 non-SCD patients. The odds ratio for AI in SCD to non-SCD patients [(12/62)/(1 340)] was 259. The odds ratio for the prevalence of AI in SCD patients in our study (19.4%) vs. the general population (approximately 0.008%) was 2 375.AI occurred in 19.4% of SCD patients included in this study. These patients thus have a 2 375-fold higher risk of developing AI than the general population, and a 259-fold greater risk of developing AI than do hospitalized non-SCD patients.
Keywords: adrenal insufficiency; sickle cell disease; cosyntropin test